A SURVEY OF PHYSICO-CHEMICAL CHARACTERISTICS AND MACROINVERTEBRATE COMMUNITIES OF THREE CONTRASTING STREAMS IN DADIN KOWA, GOMBE STATE, NIGERIA - Umar, D.M; Dantata, A. G; Mbaya, L. A; Mbimbe, E. Y; Umar, A. M; Wasa, A. A, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
A survey of physico-chemical characteristics and macroinvertebrate communities in three contrasting streams in Dadin Kowa was carried out between March and June 2016. Physicochemical parameters (i.e. temperature, pH, conductivity, turbidity, depth and width) and macorinvertebrates were sampled forthnightly. It was observed that physico-chemical characteristics of the three streams did not differ much except for conductivity which was highest in stream B and lowest in stream A. Record showed five major taxa (Odonata, Coleoptera, Hemiptera, Mollusca and the amorphous species) in the 3 streams. The macroinvertebrate community composition observed were; Gomphidae 52.38% , Dyticidae 28.57%, Notonectidae 9.52%, Melanoides tuberculatus 7.14% and Amorphous species 2.38%. Results obtained reveals that macroinvertebrate community composition differed between agricutural and urban streams. Land use activities taking place in the area might have influenced these changes. There is the need to regulate the use of agrochemicals and methods of effluents discharge into aquatic system.